PEREMPUAN DALAM HUKUM PIDANA DI INDONESIA (KAJIAN FEMINIST LEGAL THEORY) - Berliantha, Berliantha; Fasya, Ilma Ainun Nabila (IBLAM LAW REVIEW, 2023)
Feminist Legal Theory is a legal theory that was born during the second wave of the feminist movement in America. The main object of study of the Feminist Legal Theory (FLT) is criticism of patriarchal and discriminatory legal products. Legal products in Indonesia are not immune from such problems, even though the constitution has mandated in Article 27 paragraph (1) of the 1945 Constitution which confirms that every citizen has the same position before the law. However, there are several articles or verses that are enigmatic and not in favor of women. The purpose of this study is to analyze law in Indonesia, especially criminal law with the study of Feminist Legal Theory to find out how far criminal law accommodates justice for women. In addition, it can also be seen where the problem of injustice for women is in the formulation of criminal law in Indonesia. This study uses a normative legal research method with the approach used in solving the problem is a statutory approach (statute approach) and conceptual (conceptual approach). The results of this study indicate that although there are problems in the Criminal Code as a positive law in Indonesia, the presence of the TPKS Law is able to provide justice for women in handling and protecting criminal acts of violence against women.